Fa’āliyyah Istīrātījiyyah al-Musājalah al-Ĥalqiyyah fī Iktisāb al-Mafāhīm al-Tārikhiyyah Ladai Țullab al-Șaf al-Sābi’ al-Asāsī: فاعلية استراتيجية المساجلة الحلقية في اكتساب المفاهيم التاريخية لدى طلبة الصف السابع الأساسي - Fattah, Nida Qahtan; Ibrahim, Azhar Ali Hussein; Omer, Othman Abdulkarim (Aphorisme: Journal of Arabic Language, Literature, and Education, 2025)
This study aimed to investigate the effectiveness of the Circle Discussion strategy in acquiring historical concepts among seventh-grade basic students. The researchers adopted an experimental approach with a two-group design (experimental and control groups). The study sample consisted of 57 seventh-grade female students from Soz Elementary School, distributed into two groups: the experimental group (32 students) who studied using the Circle Discussion strategy, and the control group (25 students) who studied using the conventional method. A historical concepts acquisition test consisting of 36 items was developed, distributed across three levels (definition, discrimination, and application). The results showed a statistically significant difference at the 0.05 level between the mean scores of the two groups in favor of the experimental group, where the experimental group's mean was (28.06) compared to (24.12) for the control group. The effect size calculation using eta squared showed a value of (0.206), indicating a very large effect of the strategy. The study concluded that the Circle Discussion strategy is effective in improving the acquisition of historical concepts among students.